The Kuroshio bifurcation associated with islands at the Luzon Strait. Issue 11 (4th June 2016) - Sun, Ruili; Wang, Guihua; Chen, Changlin
Abstract: Based upon a suite of satellite and hydrology data along with numerical model simulations, the Kuroshio is found to be separated into two branches. The two branches are located on the western and eastern sides of the Batanes Islands. The western branch, which is the main branch of the Kuroshio, is estimated to carry roughly 68% of the transport, while the eastern branch, which has not been reported before, carries the remainder. Both branches bring warmer water northward, producing two separate warm tongues east of the Luzon Strait. The western warm tongue has an obvious seasonal variation due to the seasonal variation of the Kuroshio in the northern Luzon Strait, while the eastern warm tongue is associated with Pacific mesoscale eddies. As an anticyclonic (a cyclonic) eddy approaches the Batanes Islands from the east, the eastern branch of the Kuroshio is strongly intensified (weakened), and a more (less) pronounced warm tongue is induced. Consequently, interannual variability of Pacific mesoscale eddies affects the strength of the eastern branch. Key Points: First reporting of the Kuroshio being separated into two branches The Kuroshio bifurcation results in two warm tongues to the east of the Luzon Strait The variability of the eastern branch is associated with Pacific mesoscale eddies